(untitled) (International Journal of World Civilizations and Philosophical Studies, 2024)
Ibn Khaldun’s theories have exerted a lasting influence on the Islamic world and are highly esteemed by contemporary scholars. Despite the significance of his insight, Khaldun’s views on human nature have been underexplored in academic research. This study delves into his perspective on human nature as presented in the Muqaddimah. Using qualitative methods, this study aims to elucidate how Ibn Khaldun’s conceptualization of human nature impacts the development of human civilization. The findings concluded that human nature consists of good, evil, and a balance of both, influenced by social environment, education, and religion, with a tendency towards goodness. He critiques the moral decay in luxury-bound sedentary societies, linking it to the collapse of civilizations. Studying Khaldun’s perspectives on human nature is crucial for understanding societal development and leadership, with cross-cultural comparisons providing valuable insights.